2008
DOI: 10.1504/ijart.2008.022365
|View full text |Cite
|
Sign up to set email alerts
|

Rapid development of tangible interactive appliances: achieving the fidelity/time balance

Abstract: STEVE GILL is a product designer with 15 years experience in industry and academia. He is a Principal Lecturer at the University of Wales Institute Cardiff and Director of the Programme for Advanced Interactive Prototype Research (PAIPR) within The National Centre for Product Design & Development Research (PDR). He has designed or product managed around 50 products to market and has published 20 academic journal and conference papers. Steve has a range of research interests related to product design and develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
(16 reference statements)
1
11
0
Order By: Relevance
“…The IE Units allow rapid prototyping without the usual electronics or programming prerequisites and have been used to empirically measure the performance of real products against physical and virtual prototypes. The results show that the link between the physical act of holding a product and interaction was more marked than has previously been understood (Gill et al, 2008), thus highlighting the need for understanding the precise nature of physicality in the design process. This led to our recent work on physigrams -a diagrammatic notation based on a formal framework for mapping the relationship between physical devices and their corresponding physical actions for designers' use (Dix et al, 2009).…”
Section: Motivationmentioning
confidence: 79%
“…The IE Units allow rapid prototyping without the usual electronics or programming prerequisites and have been used to empirically measure the performance of real products against physical and virtual prototypes. The results show that the link between the physical act of holding a product and interaction was more marked than has previously been understood (Gill et al, 2008), thus highlighting the need for understanding the precise nature of physicality in the design process. This led to our recent work on physigrams -a diagrammatic notation based on a formal framework for mapping the relationship between physical devices and their corresponding physical actions for designers' use (Dix et al, 2009).…”
Section: Motivationmentioning
confidence: 79%
“…However, if a simulated or quasi-contextual environment can provide an accurate notion of product interaction then such a strategy has the potential to reduce observation cost. Previous research has suggested that lower levels of fidelity in both the operating environment and prototype products still have the potential to provide accurate usage information (Woolley et al, 2010;Gill et al, 2008;Gordon & Wilgeroth, 2008). Because of the contentious nature of this proposition, the authors refer to such observation as 'ethnography inspired' to demonstrate that there is no claim of this model providing true ethnographic enquiry.…”
Section: Situating Observationsmentioning
confidence: 99%
“…The study set out to discover if results of a user trial with a tangible prototype were more similar to the final product than a software-only prototype, and the subsequent level of fidelity required of this prototype (Gill, et al, 2008). In total, four prototypes were constructed and compared to a final device.…”
Section: Case Study 2 -Mobile Home Phonementioning
confidence: 99%